Protective Effect of TNFRSF11A rs7239667 G > C Gene Polymorphism on Coronary Outcome of Kawasaki Disease in Southern Chinese Population - Zhang, Linyuan; Lin, Kun; Wang, Yishuai; Yu, Hongyan; Li, Jinqing; Fu, Lanyan; Xu, Yufen; Wei, Bing; Mai, Hanran; Jiang, Zhiyong; Che, Di; Pi, Lei; et al. (Frontiers in Genetics, 2021)
Background: The main symptoms of Kawasaki disease (KD) are inflammatory vasculitis characterized by fever lasting one to two weeks, failure to respond to antibiotic treatment, conjunctivitis, redness of the lips and mouth, strawberry tongue, and painless enlargement of the neck lymph nodes. Studies have shown that tumor necrosis factor (TNF) and TNF receptor family members are abnormally expressed in the acute phase of Kawasaki disease, also revealing that the two have a significant role in the pathogenesis of KD. The purpose of our study was to determine the relationship between TNFRSF11A rs7239667 and the pathogenesis of KD and Coronary artery lesions in KD. Methods and Results: In this study, TNFRSF11A (rs7239667) genotyping was performed in 1396 patients with KD and 1673 healthy controls. Our results showed that G > C polymorphism of TNFRSF11A (rs7239667) was not associated with KD susceptibility. After gender and age calibration, we found that the P value of TNFRSF11A rs7239667 in male patients was 0.0418, OR = 0.79,95%CI =0.64-0.99, adjusted P=0.0425, adjusted OR = 0.80, adjusted 95%CI= 0.63-1.00. TNFRSF11A rs7239667 genotyping was performed in 408 Kawasaki disease patients with CAA and 988 KD patients without CAA. Odds ratios (ORs) and 95% confidence intervals (CIS) were also used to assess the strength of the association. We found that TNFRSF11A rs7239667 C allele significantly reduced the risk of CAA in patients with Kawasaki disease (GC vs. GG: adjusted OR = 0.99, 95%CI = 0.76-1.29,P = 0.9058;CC vs GG: After adjustment OR = 0.690,95%CI = 0.49-0.99,P = 0.0302;GC/CC vs GGP: OR = 0.90, 95%CI = 0.70-1.16,P=0.3821;CC vs GC/GG: adjusted OR = 0.7, 95%CI = 0.51-0.95,P=0.0164. Conclusion: Our study suggests that TNFRSF11A rs7239667 G > C polymorphism maybe play a protective gene for the severity of KD coronary artery injury and is related to age, which has not been previously revealed.